EnviroArt Project: Solving the Record of the Contemporary Intangible Light Phenomenon from the Immersive Technomuseographic Perspective. - Crespillo Marí, Leticia (Peter Lang, 2024)
The specific nature of contemporary light installations and environments, which require the presence of the viewer to establish a full understanding of the artistic event, raises several issues related to their documentation and cataloguing. These problems are exacerbated in environments that use light as an aesthetic resource because of its intangible, theatrical and performative character. This problem has compelled us to explore alternatives to traditional catalogues, both in printed and online versions. Hence, this text focuses on alternative modalities offered by virtual and immersive reality technologies. Virtual reality enables participation in simulated environments in ways similar to everyday reality, thus allowing us to obtain greater knowledge of the phenomenon of light and its influence on perception during the aesthetic reception of the subject in question in situ, which is impossible to experience without its presence. Art history needs to explain certain plastic phenomena that traditional cataloguing cannot because of its two-dimensional nature. Virtuality allows us to enter a built environment through our physical body, our movement and our appreciation of the artistic fact in a technologically equivalent space in which we can acquire a greater amount of information. This helps us fully understand these manifestations of art. The aim of this research is to propose an alternative method of cataloguing for this specific class of interventions, thus allowing for a comprehensive aesthetic experience through the interactive and immersive tools of 3D visualization and virtual reality, which are used in current museography.
https://www.peterlang.com/repository-policy/ (12 meses de embargo a partir de la fecha de publicación)
Ecosistema de datos abiertos y enlazados del subsector cultural de las exposiciones artísticas: formalización ontológica, soluciones tecnológicas y modelos de explotación para la generación de conocimiento y valor en el ámbito de las ICC (PY20_00508)
Keywords: Arte - Historia; Exposiciones - Diseño; Museos - Trabajos técnicos; Arte contemporáneo; Arte multimedia; Light art; Realidad virtual; Museografía; Light Art Contemporáneo; Museos; Historia del arte